PELATIHAN DESIGN THINKING UNTUK MENGENALKAN TAHAPAN DESAIN PRODUK INDUSTRI PADA SISWA SMA - Ahmad; JP, Rafeal; A, Kenneth; D.R, Adelia (Jurnal Serina Abdimas, 2024)
This activity aims to provide an understanding of entrepreneurship and product design by providing examples around you to use as business ideas. Delivery of activities is carried out face to face in the room provided by the partner. Activities are carried out in the form of lectures with design examples. The participants were very enthusiastic about listening to the lecture materials presented. Several main aspects, such as the benefits of the PKM material provided, were considered very good by the participants. The results of the questionnaire also stated that participants felt this activity was delivered well. 92% of the students rated the PKM Team's explanation as very good, while in terms of the benefits of the training, 82% of the participants rated it as good. For understanding how to capture consumer needs, understanding the design process, and understanding entrepreneurship, respectively, they were rated very good at 96%, 82%, and 86%. ABSTRAK Kegiatan ini bertujuan memberikan pemahaman tentang kewirausahaan dan desain produk dengan memberi contoh-contoh di sekitar untuk dijadikan ide usaha. Penyampaian kegiatan dilakukan dengan tatap muka di ruangan yang disediakan oleh mitra. Kegiatan dilakukan dalam bentuk ceramah dengan contoh-contoh desain. Para peserta sangat antusias mendengarkan ceramah materi-materi yang disampaikan. Beberapa aspek-aspek yang utama seperti manfaat materi PKM yang diberikan dinilai sangat baik oleh peserta. Hasil kuesioner juga menyatakan bahwa kegiatan ini dirasakan peserta disampaikan dengan baik. penjelasan Tim PKM 92% dinilai sangat baik oleh siswa, sedangkan dari aspek manfaat pelatihan 82% peserta menilai baik. Untuk pemahaman tentang bagaimana menangkap kebutuhan konsumen, memahami proses desain, serta memahami kewirausahaan masing-masing dinilai sangat baik 96%, 82%, dan 86%.